Evaluating and Comparing the Bending Performance of RC Beams Fabricated with Lightweight Aggregate Concrete and Normal Concrete of Equivalent Strength - Kamyar Narimanifar; Seyed Arash Mousavi Ghasemi (Buildings)
The construction industry continually seeks to optimize the materials used in building projects to balance structural integrity with economic and environmental concerns. Particularly in urban high-rise construction and seismic zones, the choice of material can significantly affect the project’s feasibility and safety. This study investigated the mechanical response of regular and lightweight concrete to bending stresses, which are critical factors in the structural design process. By comparing the strain–stress relationships, densities, and deformation capacities of these two varieties of concrete, this research aimed to clarify their fundamental differences. Lightweight concrete, with its lower density of 1800 kg/m3, offers noticeable weight reductions, thus presenting a viable solution for structures where reduced mass is beneficial, such as in areas with load-bearing limitations or for components that require ease of transportation and assembly. However, this study found that the reduction in weight is accompanied by lower compressive and flexural strength compared to normal concrete, which, with a density of 2400 kg/m3, exhibited greater mechanical strength and resilience under bending stresses. Stress–strain graphs generated from the experimental data illustrated both types of concrete’s elastic and plastic deformation behaviors, highlighting the material’s transition from elasticity to plasticity at specific stress points. This nuanced understanding of the materials’ behaviors is vital for construction professionals as it equips them with the information necessary to make informed decisions on material selection, ensuring safety, sustainability, and cost-effectiveness in construction projects.